REPORT OF THE 1950 PRESIDENT. - Mason, Perry (The Accounting Review, 1951)
Abstract The article presents a report on the American Accounting Association. It states that the large increase in membership among the non-teaching accountants, which took place a few years ago, has been maintained and a substantial number of new members have joined the association. The journal, The Accounting Review, under the editorship of Frank P. Smith, has continued to serve instructors, students and practitioners with a series of significant and helpful articles, book reviews, solutions to certified public accountant (CPA) examination problems, and news items of members of the association. The association has established closer relations with the Controllers Institute of America and with the Institute of Internal Auditors, which should lead to significant results during the coming year. The Membership Committee is the largest committee of the association. Each state and the District of Columbia, as well as Canada, has a member on this committee. Special attempts have been made to increase the number of teacher members, while welcoming the professional, governmental and industrial accountants who are interested in joining the association.